3D underwater scene reconstruction through descattering and colour correction. (2016) - Lu, Huimin; Li, Yujie; Serikawa, Seiichi; Li, Xin; Li, Jianru; Li, Kuan-Ching
This paper describes a novel method for ocean scene 3D reconstruction. While light is travelling through water, light rays are distorted depending on the wavelength. That is, absorption, scattering and colour distortion are three major distortion issues for underwater optical imaging. Scattering is caused by large suspended particles, as in turbid water that contains abundant particles, which causes the degradation of the captured image. Colour distortion corresponds to the varying degrees of attenuation encountered by light travelling in water at different wavelengths, causing ambient underwater environments to be dominated by a bluish tone. Our key contributions proposed here include a novel deep-sea imaging model to compensate for the attenuation discrepancy along the propagation path and an effective underwater scene 3D reconstruction method. The recovered 3D images are characterised by a reduced noise level, better exposure of the dark regions, and improved global contrast where the finest details and edges are enhanced significantly.